Curriculos como redes de saberesfazeres e as invenções cotidianas que potencializam a vida - Vargas, Cristina Lens Bastos de (2012)
This research aims to problematize the knowing-how-to- do nets woven by the students in the public school every day life in the county of Cachoeiro de Itapemirim. As it visits its space-times, it reflexes on the threads of the complex nets woven inside the school: listening to people and talking to them, in search of perceiving the relationship between the syllabus and the ‘routine’ of the school. What really matters, in this study, is the awareness that results from the meetings in the school limits, with attention to the common practices, searching for what is not always visible: rethinking the new, not in the sense of doing what is new, but in the sense of seeing the syllabus with other senses, and so that it can be thought of, in other ways. It is under such perspective that the happenings will be problematized, and also the threads of the complex nets woven inside the school. Thus, it is an attempt to perceive what occurs in that space and when the school takes the National and Municipal Curriculum referential in order to use them in the school praxis. As one experiences those environments, it is possible to notice that it is common the existence of official normative documents in the school (they are essential). However, it can be analyzed, taking into account the possibilities and the experiences that go inside that universe. It is understood that there is no starting point in the nets. The intention is provoking a look, considering the studies on syllabus in the nets, perceiving the multiplicity of the varieties in which the syllabus exists. This way, this work intends to investigate how the syllabus process occurs in that school, in order to make evident, in its nets, the knowing-how-to –do creative possibilities, which value the school, and the experiences of the teachers and of the students. These are woven every day, visiting its spaces-times, listening to people, talking to them in order to perceive the creative possibilities that value the school.